PREVALENCE OF HEPATITIS B SURFACE ANTIGEN CARRIER STATE IN PATIENTS WITH LICHEN PLANUS-REPORT OF 200 CASES FROM LAHORE, PAKISTAN - Mahboob, Atiya; Haroon, Tahir Saeed; Iqbal, Zafar; Saleemi, Munir Akhtar; Munir, Asma (Journal of Ayub Medical College Abbottabad, 2007)
Background: To determine the prevalence of hepatitis B surface antigen carrier state in patients with lichen planus. Methods: A quasi experimental cross sectional study was done at Department of Dermatology, Shaikh Zayed Federal Postgraduate Medical Institute, Lahore, Pakistan, from April 2003 to March 2005. Two hundred clinically diagnosed cases of LP and equal number of patients with other dermatoses not reportedly associated with hepatitis B virus (HBV) infection (control group) were collected from Skin Out Patient Department. They were screened for hepatitis B surface antigen (HBsAg) by Enzyme Linked Immunosorbent Assay (ELISA). Statistical analysis was done by using SPSS package version 11. Results: Out of 200 patients of each group, three patients with LP and seven patients from control group were positive for HBsAg. The test of significance for proportions revealed that there was no significant difference (p>0.1) between two groups. Conclusion: No association between HBsAg carrier state and LP was found in our study. Key Words: Lichen Planus; Hepatitis B surface antigen.